Language and Social Psychology Approaches to Race, Racism, and Social Justice: Analyzing the Past and Revealing Ways Forward. (January 2022) - Shrikant, Natasha; Giles, Howard; Angus, Daniel
Issues of race, racism, and social justice are under-studied topics in this journal. This Prologue, and our Special Issue (S.I.) more broadly, highlights ways that language and social psychology (LSP) approaches can further our understanding of race, racism, and social justice, while suggesting more inclusive directions for their theoretical development. Acknowledging the inspiration from the Black Lives Matter (BLM) movement, we begin by discussing our deeply-held personal and emotional connections to recent societal events, including police violence against innocent Black civilians and the prevalence of anti-Asian hate. What follows, then, is: a historical analysis of past JLSP publications on these issues, a proposal for more intersections between LSP and communication social justice research, and an overview of the BLM movement together with the four articles that follow. We conclude by advocating for individual and institutional practices that can create socially-just changes by LSP scholars in the academy.